Theft Detection Unit For Photo-Votaic Generation in Smart Grid Networks - Almadani, Nouf Ahmad (2020)
A Master of Science thesis in Electrical Engineering by Nouf Ahmad Almadani entitled, “Theft Detection Unit for Photo-Voltaic Generation in Smart Grid Networks”, submitted in May 2020. Thesis advisors are Dr. Mostafa Shaaban and Dr. Usman Tariq. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).